2022
DOI: 10.1093/jac/dkab505
|View full text |Cite
|
Sign up to set email alerts
|

Delamanid or pretomanid? A Solomonic judgement!

Abstract: Given the low treatment success rates of drug-resistant tuberculosis (TB), novel TB drugs are urgently needed. The landscape of TB treatment has changed considerably over the last decade with the approval of three new compounds: bedaquiline, delamanid and pretomanid. Of these, delamanid and pretomanid belong to the same class of drugs, the nitroimidazoles. In order to close the knowledge gap on how delamanid and pretomanid compare with each other, we summarize the main findings from preclinical research on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 127 publications
0
20
0
1
Order By: Relevance
“…Previous studies by our group and other investigators reported consistent activities of nitrocompounds [19,20], including metronidazole (MTR), pretomanid (PRT, formerly PA-824) and nitazoxanide (NTZ), alone and in combination, against AR and NR Mtb [21][22][23][24][25][26]. Recent trials demonstrated the potential of PRT-containing regimens against drug-susceptible and -resistant pulmonary tuberculosis (TB) [27,28].…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies by our group and other investigators reported consistent activities of nitrocompounds [19,20], including metronidazole (MTR), pretomanid (PRT, formerly PA-824) and nitazoxanide (NTZ), alone and in combination, against AR and NR Mtb [21][22][23][24][25][26]. Recent trials demonstrated the potential of PRT-containing regimens against drug-susceptible and -resistant pulmonary tuberculosis (TB) [27,28].…”
Section: Introductionmentioning
confidence: 90%
“…However, this regimen should only be administered under operational research conditions and when BDQ and linezolid have not been previously used [ 30 ]. PMD, which is a nitroimidazole derivative similar to DLM, was the third and most recently approved drug to be added to the TB treatment arsenal [ 36 ]. The US FDA granted its approval for PMD in 2019 as a part of the BPaL regimen and limited its indication to adults with XDR-TB or non-responsive or drug-intolerant MDR-TB [ 36 ].…”
Section: Challenges To the Global Control Of Tbmentioning
confidence: 99%
“…Under normoxic conditions, pretomanid is converted into reactive intermediates that interfere with mycolic acid synthesis, while in anaerobic environments, it acts as an NO donor that effectively poisons the respiration of mycobacteria. 15,16 By combining bedaquiline, pretomanid, and linezolid, a new therapeutic regimen for treatment of MDR tuberculosis has been established. 17 NTM have come into scientific focus in recent years, owing to the fast-growing, multidrug-resistant Mabs and the Mycobacterium avium complex (MAC), which have emerged as problematic opportunistic pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Research efforts have led to the approval of two new drugs: bedaquiline and pretomanid. − Bedaquiline acts by inhibiting mycobacterial ATP synthase, while pretomanid has a rather complex mechanism of action. Under normoxic conditions, pretomanid is converted into reactive intermediates that interfere with mycolic acid synthesis, while in anaerobic environments, it acts as an NO donor that effectively poisons the respiration of mycobacteria. , By combining bedaquiline, pretomanid, and linezolid, a new therapeutic regimen for treatment of MDR tuberculosis has been established …”
Section: Introductionmentioning
confidence: 99%